The Effect Of Live Streaming, Brand Image, And Product Quality On Purchasing Decisions On The Tiktok Platform Bromen Products In Surabaya - Maghfiroh, Mutiara Lailatul; Pudjoprastiono, Hery (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The development of live streaming activities on e-commerce platforms has changed the way consumers make purchasing decisions. This study aims to analyze the effect of live streaming, brand image, and product quality on purchasing decisions on Bromen products in Surabaya. This study used a quantitative approach by distributing questionnaires to 105 respondents and analyzing them using the Partial Least Square (PLS) method. The results showed that live streaming and product quality had a positive and significant effect on purchasing decisions, while brand image had no significant effect. This finding indicates that aspects of live interactivity and product quality are more decisive than perceptions of brand image in shaping purchasing decisions in the digital era.